Efektivitas Mikroemulsi O/W dengan Surfaktan Non Ionik dalam Menghambat Fotooksidasi Vitamin C pada Model Minuman - Lutfi Suhendra; Sri Raharjo; Pudji Hastuti; Chusnul Hidayat (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2013)
The objective of this study was to obtain the effectiveness of oil-in-water (o/w) microemulsion using nonionic surfactans to improve the stability and inhibit the deterioration rate of vitamin C in beverage model systems caused by photooxidation. O/W microemulsions were formulated with oil-surfactan ratio (15:85 v/v), with surfactant mixture consisting of Tween 80:Span 80:Tween 20 = 92:5.5:2.5 (% v/v) and water content 65%. O/W microemulsions were subjected to stability towards pH and dilution. The dilution were done by dilute microemulsions with water and citrate buffer (pH: 3.5; 4.5 and water pH 6.5) with proportion 1:1, 1:9 and 1:99. The microemulsios were tested the stability on heating treatment at 105 °C for 5 hours and during storage for 8 weeks at room temperature. The baverage models were vitamin C solution (450 mg/L, citric acid (1%) and sucrose (6%). The o/w microemulsions added in the beverage models were microemulsion that had been diluted 50 and 100 times with water pH 6.5. The beverage model was added with 5 ppm erythrosin as sensitizer and without erythrosin as control. The models were exposed to ﬂ ourescent light with an intensity of 2000 lux. Vitamin C concentration was mesured by the method of riboﬂ avin-sensitized photodynamic UV spectrophotometry every 2 hours. The o/w microemulsion was stable at pH 3.5 to 6.5 and dilution (1:1, 1:9, and 1:99), heating and storage. The o/w microemulsions which were diluted 100 times effectively increased the stability of vitamin C, but the o/w microemulsions diluted 50 times was more efective to inhibit the rate of distruction of vitamin C due to photooxidation in beverage model.ABSTRAKTujuan penelitian adalah memperoleh efektivitas mikroemulsi o/w dengan surfaktan non ionik untuk meningkatkan stabilitas dan menghambat laju kerusakan vitamin C akibat fotooksidasi pada model minuman. Mikroemulsi oil-inwater (o/w) dibentuk dari campuran minyak–surfaktan (15:85 v/v) dengan perbandingan surfaktan Tween 80:Span 80:Tween 20 = 92:5,5: 2,5 (% v/v) dengan kadar air 65%. Mikroemulsi o/w diuji stabilitas terhadap pH dan pengenceran dengan cara mengencerkan mikroemulsi dengan media air dan buffer sitrat (pH: 3,5; 4,5 dan aquades pH 6,5) dengan proporsi 1:1. 1:9 dan 1:99, selanjutnya mikroemulsi o/w yang telah dilakukan pengenceran dengan pH berbeda ini diuji stabilitasnya pada pemanasan 105 °C selama 5 jam dan stabilitas penyimpanan selama 8 minggu pada suhu ruang. Model minuman terdiri dari larutan vitamin C (450 mg/L), asam sitrat (1%) dan sukrosa (6%). Mikroemulsi o/w yang ditambahkan ke dalam model minuman adalah mikroemulsi diencerkan 50 kali dan 100 kali dengan aquades pH 6,5. Selanjutnya ditambahkan dengan/tanpa eritrosin sehingga masing-masing larutan mengandung eritrosin 5 ppm sebagai sensitiser. Sampel tersebut kemudian dipapar dengan lampu ﬂ uoresen dengan intensitas cahaya 2000 lux. Konsentrasi vitamin C diukur dengan metode riboﬂ avin-sensitized photodynamic UV spectrophotometry tiap 2 jam. Mikroemulsi o/w stabil pada pH 3,5 sampai 6,5 dan pengenceran (1:1. 1:9 dan 1:99), pemanasan dan penyimpanan. Mikroemulsi o/w diencerkan 100 kali efektif meningkatkan stabilitas vitamin C, namun mikroemulsi o/w diencerkan 50 kali lebih efektif untuk menghambat laju kerusakan vitamin C akibat fotooksidasi pada model minuman.